Effect of extracorporeal shockwave therapy on carpal tunnel syndrome: A systematic review and meta-analysis of randomized controlled trials. Issue 33 (August 2019) - Kim, Ju Chan; Jung, Se Hee; Lee, Shi-Uk; Lee, Sang Yoon
Abstract: Background: Although several trials have reported the use of extracorporeal shock wave therapy (ESWT) for mild to moderate carpal tunnel syndrome (CTS), little is known about the efficacy of ESWT. Thus, we performed a meta-analysis to evaluate whether ESWT can improve symptoms, functional outcomes, and electrophysiologic parameters in CTS. Methods: Six randomized controlled trials investigating the effect of ESWT on CTS were retrieved from PubMed, Embase, and the Cochrane Library. We performed a pairwise meta-analysis using fixed- or random-effects models. Results: ESWT showed significant overall effect size compared to the control (overall Hedge g pooled standardized mean difference (SMD) = 1.447; 95% confidence interval [CI], 0.439–2.456; P  = .005). Symptoms, functional outcomes, and electrophysiologic parameters all improved with ESWT treatment. However, there was no obvious difference between the efficacy of ESWT and local corticosteroid injection (pooled SMD = 0.418; 95% CI, −0.131 to 0.968; P  = .135). A publication bias was not evident in this study. Conclusion: Our meta-analysis revealed that ESWT can improve symptoms, functional outcomes, and electrophysiologic parameters in patients with CTS. Further research is needed to confirm the long-term effects and the optimal ESWT protocol for CTS. Abstract : Supplemental Digital Content is available in the text